THE MURDERS IN THE RUE MORGUE: NEUROSIS - Langhoff, Darius (Acta Neophilologica, 2008)
The article deals with E.A. Poe’s story The Murders in the Rue Morgue which centers on a mysterious murder case. Several acknowledged critical appreciations of the tale are presented and reevaluated. The paper endeavors to uncover inconsistencies in the traditional critical appro- aches as well as to unveil Poe’s sporadic literary incongruities embedded in the text. Stress is laid on the contrast between the traditional psychoanalytical readings of the story and the views of modern psychology and psychiatry. The article is intended to shed an alternative light on possible interpretations of the tale written by the 19th century pioneer in the field of the detective story and novel.